Roba Hassan. The Effect and Effectiveness of Remote Learning - Hassan, Roba (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. Over the course of the last several months, education systems around the world have had to quickly adapt to the growing impact of COVID-19 on the schooling of children. As many districts switched over to remote learning, there are still many imperfections in the virtual system. New research has indicated that remote learning has caused an increase of educational inequalities between well-off students and their disadvantaged counterparts, leading to the widening of the achievement gap teachers have been working hard to narrow within the classroom. There has been a recent collection of data regarding access to technological material, an appropriate learning environment, and resources that students need to succeed at the same standard they did previously in-person. This paper aims to take that research, along with a study surveying high school students currently learning online, to understand the effect and effectiveness of remote learning. When conducting this research, the ultimate goal was to see what countries around the world were doing to best accommodate their students learning from home. Moreover, based on the information and current studies regarding the pandemic and education, this article hopes to offer some suggestions that districts and governments can consider in order to enhance the learning experience during such a difficult time.